Sympatric elasmobranchs and fecal samples provide insight into the trophic ecology of the smalltooth sawfish - Poulakis, GR; Urakawa, H; Stevens, PW; DeAngelo, JA; Timmers, AA; Grubbs, RD; Fisk, AT; Olin, JA (Endangered Species Research, 2017)
Growing concerns about the conservation of elasmobranchs have prompted a surge in research, because scientific studies that can support management actions are needed. Sawfishes are among the most threatened fishes worldwide and epitomize the challenge of conserving widely distributed, large-bodied marine fishes. We used a comparative approach to provide data on the trophic ecology of the smalltooth sawfish Pristis pectinata in the western Atlantic coastal waters of southwest Florida, USA. Specifically, we applied (1) stable isotope techniques to fin tissues of smalltooth sawfish and 2 sympatric elasmobranch species that have well-documented diets (i.e. bull shark Carcharhinus leucas and cownose ray Rhinoptera bonasus), and muscle tissue from a variety of known and potential prey species; and (2) an 18S rRNA gene sequencing technique to identify prey taxa in sawfish fecal samples. These analyses provided evidence that the smalltooth sawfish feeds primarily on teleost and elasmobranch fishes at all life stages even though sawfish move from estuarine to coastal habitats during their ontogeny. Although both sawfish and bull sharks occupy estuarine waters as juveniles and are piscivorous, the results also indicate that these species partition habitat. The cownose ray has been thought of as migratory throughout its range, but these data indicate that non-migratory, estuarine populations exist at lower latitudes. Collectively, these results will aid in the development of management decisions regarding these species and in improving long-term recovery planning for the smalltooth sawfish.